Bringing local perspective into peacebuilding. The case of Sierra Leone Truth and Reconciliation Commission - Irene Jiménez-Zumalde (Revista Iberoamericana de Estudios de Desarrollo)
After going through an eleven yearlong violent civil war, Sierra Leone started its peacebuilding process in 2002. This operation has been considered a successful one. In the paper, I focus on one of its instruments: the Sierra Leone Truth and Reconciliation Commission (SLTRC). This body promoted truth telling to establish accountability and to know the needs in society. The aim was to determine to which extent it incorporated the local perspective. To this end, different ways of incorporating the local perspective have been used. At the same time, I also looked at its gender approach, where both successful and shortcomings were found. I conclude that neither of the perspective was well consolidated.